Quality of life through Quality of Information Proceedings of MIE2012 - Mantas, John (IOS Press, 2014)
Curricular recommendations coming from highly respectable associations are highly useful. Nevertheless, they show fatigue in keeping the pace of any fast evolution, as in the ICT happens. So we do the attempt to disclose the emerging challenges affecting e-Health curricular education.